Triggering factors associated with a new episode of recurrent acute anterior uveitis - Nutnicha Neti (Nature Portfolio, 2021)
Abstract To identify triggering factors for the next inflammatory episode of recurrent acute anterior uveitis (RAAU), a 1:1 case–control study was conducted. We interviewed RAAU patients with recent acute anterior uveitis attack and quiescent controls for their information during a previous month using Srithanya Stress Test (ST-5) and questionnaires about potential triggering factors. Asymptomatic controls were matched for age (± 5 years), sex, and HLA-B27. There were 39 pairs of cases and controls. Patients who recently experienced a uveitis attack demonstrated higher mean ST-5 scores (3.7 ± 2.9 vs 0.7 ± 1.1) and shorter sleep time (6.3 ± 1.4 vs 7.4 ± 0.7 h per day) compared with their controls. In the multivariate conditional logistic regression analysis, ST-5 score ≥ 3 (OR 9.07, 95% CI 1.14–72.16, p = 0.037) and sleep time < 7 h per day (OR 12.12, 95% CI 1.37–107.17, p = 0.025) were more likely to trigger a uveitis attack in RAAU accounted for patients’ age, sex, HLA- B27 positivity, and presence of concurrent anti-inflammatory drugs for co-existing diseases. Other suspected triggering factors were not found to have any significant association. In short, stress and inadequate sleep may lead to the future episode of acute anterior uveitis in RAAU. Both physical and emotional stress management should be advised to RAAU patients to minimize recurrences and further complications.